Investigating the Dimensions of Victimization in Sixth-Grade Male Students and Its Association with Subjective Well-Being in School and School Bonding - Borzoo Amirpour; Fatemeh Takallou; Danesh Valadbeigi (Shiraz University of Medical Sciences, 2024)
Background: Victimization in schools has become one of the most prevalent problems in the worldwide education system. This study explored the dimensions of victimization in sixth-grade male students in Kermanshah City, Iran and its association with subjective well-being in school and school bonding.Methods: The current study was conducted using a descriptive correlational design. The statistical population included all male students in the sixth grade in Kermanshah City, Iran in the academic year 2022-2023. A sample of 374 individuals was selected using the multi-stage cluster random sampling method. To collect information, the Multidimensional Victimization Scale (MPVS), School Bonding Questionnaire (SBQ), and Elementary School Students' Subjective Well-Being (ESSSWBSS) were administered. Pearson's correlation coefficient and multiple regression were performed using SPSS version 27 to analyze the data.Results: Pearson correlation analysis revealed a significant inverse association between victimization at school and its dimensions with subjective well-being in school (r=-0.37) and school bonding (r=-0.010). Furthermore, the results of multiple regression showed that school bonding (β=-0.15, P=0.009) and subjective well-being in school (β=-0.33, P=0.031) were significant negative explanatory variables of victimization at school.Conclusions: Risky behaviors such as feeling victimized can hinder students' educational achievements. Therefore, it is recommended that school counselors identify students who feel victimized by their peers and provide them with appropriate educational interventions and workshops to enhance their subjective well-being in school and school bonding.